The Mystical Commentary Of The Provision Verses Alusî Example - Sarıgül, Murat (Fırat University, 2018)
Alûsî in his encyclopedic commentary Rûhü'l-Meanî mentioned the symbolic commentary of verses under the title of “symbols”. On the other hand, Ziyâeddîn Hâlid Nakşibendî d.1826 has benefited from the field of Sufism. The verses of the provision, have a structure that emphasizes the more concrete facts structurally and emphasizes the true meaning in the style of expression. In this study, in this kind of verses which may be considered to be closed to symbolic commentary, the issues such as how to make the commentary, the structural features of symbolic commentary, whether it is a method and whether it is composed of signs coming to the heart are examined in Alûsî

Alûsî Rûhü'l-Meânî adlı ansiklopedik tefsirinde, işâretler başlığı altında âyetlerin işârîtasavvufi yorumlarına yer vermiştir. Diğer taraftan kendisi, Ziyâuddîn Hâlid Nakşibendî v.1826 ’den tasavvuf alanında istifade edip feyz almıştır. Ahkâm âyetleri, yapısal olarak daha somut olguları açıklayan, ifade uslûbunda hakiki manaya vurgunun yoğun olduğu, daha has özel lafızların kullanıldığı bir yapıya sahiptir. Bu çalışmada işârî yoruma kapalı olduğu düşünülebilecek bu tür âyetlerde, işârî tefsirin nasıl yapılabildiği, işârî yorumun yapısal özellikleri, bunun bir usulünün olup olmadığı ve tamamen kalbe gelen işaretlerden mi müteşekkil olduğu gibi hususlar Alûsî özelinde incelenmiştir
AHKÂM ÂYETLERİNİN İŞÂRÎ YORUMU ALUSÎ ÖRNEĞİ